Pengukuran Manajemen Risiko Teknologi Informasi dengan Metode Octtave-S - Hendarti, Henny; Maryani, Maryani (Bina Nusantara University, 2014)
The purpose of this paper is to measure risks to identify company's assets and analyze risks, and to do strategic planning of security protection and minimize risk. Research used case study by reading materials dealing with the OCTAVE-S method. Observation was done directly to the relating parties through an interview, as well as using a questionnaire based on the OCTAVE-S method. The result obtained from this research is risk management of information technology in order to minimize the risks. Based on the findings obtained, it is expected company can identify potential risks and mitigate them efficiently and effectively.